Persaudaraan Orang Manggarai yang Terkikis: Tinjauan atas Budaya Sida Manggarai Menurut Konsep Persekutuan Gabriel Marcel - Doris, Yulius Edward Indra; Hutagalung, A. Marisa Br. (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2024)
The focus in this article is to discuss the eroded brotherhood of the Manggarai people according to Gabriel Marcel's concept of Communion in the midst of the presence of the sida culture. The sida culture is a form of respect from the anak wina (sister) to the anak rona (brother) in various important events. The honor is given in the form of participation to relieve dependents in the form of money or goods. This culture has noble values that emphasize the importance of harmonious relationships between humans and each other. This research uses a comparative literature study method to explore the relationship between the Sida culture and Marcel's concept of fellowship. The findings of this study are that Sida culture and Marcel's concept of communion both initiate participation as the basis of communion. However, in Sida culture, communion is based on familial relations, while in Marcel's view, communion is based on intersubjective relations. This intersubjective relationship is what makes people open up to each other and understand each other.